ADDUCTOR POLLICIS MUSCLE THICKNESS AND PREDICTION OF POSTOPERATIVE MORTALITY IN PATIENTS WITH STOMACH CANCER - POZIOMYCK,Aline Kirjner (2018)
ABSTRACT Background: Malnutrition is very prevalent in patients with gastric cancer and increases the risk of morbidity and mortality. Adductor pollicis muscle thickness (APMT) appears as an important objective, quick, inexpensive and noninvasive measure to assess the muscle compartment Aim: To compare APMT and other nutritional assessment methods and to correlate these methods with postoperative mortality Methods: Forty-four patients, 29 men and 15 women, mean age of 63±10.2 and ranging from 34-83 years, who underwent nine (20.5%) partial and 34 (77.3%) total gastrectomies due to stomach cancer (stage II to IIIa) were preoperatively assessed by Patient Generated Subjective Global Assessment (PG-SGA), anthropometry and laboratorial profile Results: APMT better predicted death (p<0.001) on both, dominant and non-dominant hand, and well correlated with albumin (p=0.039) and PG-SGA (p=0.007) Conclusion: APMT clearly allowed to determine malnutrition and to predict risk of death in patients with gastric cancer.